Impact of Risk on the Degree of Banking Safety in Traditional Jordanian Banks (Global Journal of Management and Business Research, 2014)
This study aimed to measure the impact of banking risk which represented "liquidity risk, credit risk, and interest rate risk" on the degree of safety for traditional (commercial) Jordanian banks. A sample of Jordanian traditional banks was used during the period (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011).The methodology which used to analyze the impact of banking risks on the degree of safety in commercial banks is the multiple linear regression. The study hypotheses were tested independently for each type of risk. The results showed a statistically significant relationship between bank risk and the degree of safety for Jordanian commercial banks. The study recommended that the risk management should be subject to a continuous surveillance by the management, with focus on credit risk. Also, sources and usages of funds should be identified and determined, considering the main targets for banks. ( I.e. liquidity, profitability and safety). Developing appropriate mechanisms to deal with the bank risk, the statement of seriousness on banks and continues development of regulatory controls are also recommended.
Keywords: bank; risk; safety; traditional banks